STATUS PENGELOLAAN PERIKANAN DENGAN PENDEKATAN EKOSISTEM: APLIKASI PADA NELAYAN KECIL KEPULAUAN KEI BESAR KABUPATEN MALUKU TENGGARA (WPPNRI 718) - Makailipessy, Marvin M; Abrahamsz, James (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2023)
This study aims to analyze the status of fisheries management based on the EAFM (Ecosystem Approach for Fisheries Management) approach and to recommend improvements to fisheries management based on the results of the EAFM assessment. This research was conducted from October to November 2021 in nine villages (ohoi) which are included in 4 sub-districts on Kei Besar Island Southeast Maluku Regency. Data were collected in several ways, including interviews with household and institutional fisheries, observation, and literature studies regarding 30 indicators in six EAFM domains. The status of fisheries management using the ecosystem approach in the Kei Besar Islands is categorized as good with a total aggregate value of 61.25 (light green) obtained based on management status per domainas follows: 1. Fish resource is categorized as good; 2. The habitat/ecosystem is categorized as average; 3. Fishing techniques are categorized as average; 4. Social is categorized as good; 5. Economic is categorized as good; and 6. Institutional is categorized as good. Management improvements should focus on: 1. Habitat and ecosystem domain, precisely the status of seagrass and mangrove ecosystems; 2. Fishing techniques domain on indicators such as fishing capacity and fishing effort, suitability of functions and size of vessels, and certification of fishing vessel crews; 3. Social domain on stakeholder participation indicators; and 4. Economic domain on household income indicators (RTP) by considering other domains and indicators. ABSTRAK Penelitian bertujuan untuk menganalisis status pengelolaan perikanan berdasarkan pendekatan EAFM (Ecosystem Approach for Fisheries Management) serta merekomendasikan perbaikan pengelolaan perikanan berdasarkan hasil penilaian EAFM. Penelitian ini dilakukan pada bulan Oktober – Nopember 2021 pada 9 ohoi/desa yang termasuk dalam 4 kecamatan yang berada pada Pulau Kei Besar Kabupaten Maluku Tenggara. Pengumpulan data dilakukan melalui wawancara rumah tangga perikanan dan kelembagaan, observasi serta studi literatur terhadap 30 indikator pada enam domain EAFM. Status pengelolaan perikanan dengan pendekatan ekosistem di Kepulauan Kei besar Kabupaten Maluku Tenggara berada pada kategori baik dengan nilai agregat total sebesar 61,25 (hijau muda) yang diperoleh berdasarkan status pengelolaan per domain, masing-masing: 1. Domain sumberdaya ikan dalam kategori baik; 2. Domain habitat/ekosistem dalam kategori sedang; 3. Domain teknik penangkapan ikan dalam kategori sedang; 4. Domain sosial dalam kategori baik; 5. Domain ekonomi dalam kategori baik; dan 6. Domain kelembagaan dalam kategori baik. Upaya perbaikan pengelolaan harus lebih difokuskan pada: 1. Domain habitat dan ekosistem khususnya status ekosistem lamun dan mangrove; 2. Domain teknik penangkapan ikan pada indikator kapasitas perikanan dan upaya penangkapan, kesesuaian fungsi dan ukuran kapal, serta sertifikasi awak kapal perikanan; 3. Domain sosial pada indikator partisipasi pemangku kepentingan; dan 4. Domain ekonomi pada indikator pendapatan rumah tangga (RTP) dengan atau harus mempertimbangkan domain dan indikator lainnya. Kata Kunci: EAFM, sumberdaya ikan, nelayan, sosial ekonomi, Pulau Kei Besar